1996
DOI: 10.1029/96wr01779
|View full text |Cite
|
Sign up to set email alerts
|

Models of the water retention curve for soils with a fractal pore size distribution

Abstract: The relationship between water content and water potential for a soil is termed its water retention curve. This basic hydraulic property is closely related to the soil pore size distribution, for which it serves as a conventional method of measurement. In this paper a general model of the water retention curve is derived for soils whose pore size distribution is fractal in the sense of the Mandelbrot number‐size distribution. This model, which contains two adjustable parameters (the fractal dimension and the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
0
11

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(91 citation statements)
references
References 31 publications
8
72
0
11
Order By: Relevance
“…This is due in part to the relatively small number of parameters that can define a random fractal porous medium of great complexity and rich structure. Also, fractal scaling of natural porous media has been widely anticipated on the basis of the observed power law form of soil water retention curves [Ahl and Niemeyer, 1989;Tyler and Wheatcraft, 1990;Rieu and Sposito, 1991a, 1991b, 1991cPerrier et al, 1996;Perfect, 1999]. There has been considerable debate about the validity of the approaches presented in these papers because they generally neglect pore connectivity [Bird et al, 1996;Rieu and Perrier, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…This is due in part to the relatively small number of parameters that can define a random fractal porous medium of great complexity and rich structure. Also, fractal scaling of natural porous media has been widely anticipated on the basis of the observed power law form of soil water retention curves [Ahl and Niemeyer, 1989;Tyler and Wheatcraft, 1990;Rieu and Sposito, 1991a, 1991b, 1991cPerrier et al, 1996;Perfect, 1999]. There has been considerable debate about the validity of the approaches presented in these papers because they generally neglect pore connectivity [Bird et al, 1996;Rieu and Perrier, 1998].…”
Section: Introductionmentioning
confidence: 99%
“…Maus et al (1999) conducted variogram analysis on magnetic data in Canada and found the data to exhibit scaling behavior as function of the horizontal distance. Studies in the soil science field have shown that the soil pore structure is fractal (Perrier et al 1996;Baveye et al 1998). Scaling behavior has also been noted for subsurface properties (namely the intrinsic permeability, K) as a function of space.…”
Section: Multifractal Modeling and Magnetic Datamentioning
confidence: 97%
“…We then seek for functions whose Laplace transforms are analytically obtained and asymptotes for sufficiently large t* are @*(t*) --f a3t*-5/2 and (a3 and a4 are constants) in models 3 and 4, respectively. The functions (22) we have chosen are @*(t*) = 4!4e~p(t')I~Erfc(t*'/~) (model 3), (12) @*(t*) = 4 e~p ( t * ) l~E r f c ( t * ' /~) (model 4), (13) …”
Section: Theorymentioning
confidence: 99%